Physiologic correlates of tricuspid annular plane systolic excursion in 1168 healthy subjects. (15th November 2016) - Ferrara, Francesco; Rudski, Lawrence G.; Vriz, Olga; Gargani, Luna; Afilalo, Jonathan; D'Andrea, Antonello; D'Alto, Michele; Marra, Alberto M.; Acri, Edvige; Stanziola, Anna Agnese; Ghio, Stefano; Cittadini, Antonio; et al.
Abstract: Background: TAPSE provides a simple, reproducible estimate of the longitudinal function of the right ventricle (RV). However, the normal limits and physiologic correlates of tricuspid annular plane systolic excursion (TAPSE) are not exactly known. The aim of this study was to explore the full spectrum of TAPSE values and determine the physiologic correlates of TAPSE. Methods and results: From June 2007 to December 2013, 1168 healthy subjects [mean age 45.1 ± 16 years, range 16 to 92; 555 (47.5%) men] underwent comprehensive transthoracic echocardiography (TTE) as recommended by current guidelines. TAPSE values were higher in men than women (24.0 ± 3.5 vs 23.2 ± 3.0 mm, p value < 0.0001) but did not vary according to age. On multivariable linear regression analysis, cardiac output, RV basal and longitudinal dimensions were the only variables independently associated with TAPSE (β coefficient = 0.161, 0.116 and 0.115 respectively). On the other hand echocardiographically-derived systolic pulmonary artery pressure (SPAP), pulmonary vascular resistance and mitral E/e′ ratio were significantly higher in older subjects. Therefore a significant decrease of TAPSE/SPAP was detected in > 60 years old cohort ( p  = 0.0001). Conclusions: Our large cohort of healthy subjects provides sex and age-based TAPSE and TAPSE/SPAP normal cut-offs. TAPSE was found to be higher in men but not influenced by age. It was mainly correlated with echo-Doppler indices reflecting pre-load as opposed to afterload. On the other hand a significant decrease of TAPSE/SPAP with older age was registered as a direct consequence of increased SPAP with aging.